Վարակիչ հիվանդությունների համաճարակաբանական առանձնահատկությունները մանկական բազմապրոֆիլ հիվանդանոցի ընդհանուր հիվանդացության կառուցվածքում - Կ. Ս. Քոչարյան (Հայաստանի ԳԱԱ)
Цель работы – изучение эпидемиологических особенностей инфекционных заболеваний в структуре общей детской заболеваемости в трехлетней динамике. Исследования проводились в одной из крупнейших детских больниц Еревана в течение 2013-2015 гг.The purpose of the study was to reveal the epidemiological features of infectious diseases in the structure of childrens’ common morbidity in the threeyears’ dynamics. The studies were conducted in one of the largest children's hospital in Yerevan during the 2013-15 years’ period.
Keywords: Medicine; Epidemiology